Emerging technologies in agricultural engineering - Goyal, Megh Raj (Waretown, NJ : Apple Academic Press, 2017)
"This book covers an array of issues on emerging agricultural engineering and technology, featuring new research and studies. The volume is broken into three parts: emerging technologies, energy management in agriculture, and management of natural resources, in which particular attention is paid to water management, a necessary consideration for successful crop production, especially in water-scarce regions. Topics include: alleviating drainage congestion solar energy for agriculture anaerobic digestion by inoculation with compost self-propelled inter-cultivators agrobiodiversity watershed development and management This volume offers academia, engineers, technologists, students, and others from different disciplines information to gain knowledge on the breadth and depth of this multifaceted field of agricultural engineering. There is an urgent need to explore and investigate the current shortcomings and challenges of the current innovations and challenges. "--Provided by publisher.
part, Emerging Technologies / Megh R. Goyal -- chapter 1 Drainage Congestion in Hirakud Command, Odisha: Issues and Opportunities to Augment Crop Production / Megh R. Goyal Balram Panigrahi Jagadish Chandra Paul Kajal Panigrahi -- chapter 2 Irrigation Technology Options for Selected Agricultural Crops / Megh R. Goyal Vishal K. Chavan -- part, Energy Management in Agriculture / Megh R. Goyal -- chapter 3 Solar Energy: Principles and Applications / M. K. Ghosal -- chapter 4 Enhanced Anaerobic Digestion by Inoculation With Compost / Zhiji Ding Nirakar Pradhan Willy Verstraete -- chapter 5 Tractor Utilization in Vidarbha Region, India / D. V. Tathod Y. V. Mahatale V. K. Chavan -- chapter 6 Performance of Reversible Mold Board Plow / Yogesh V. Mahatale Dnyaneshwar V. Tathod Vishal K. Chavan -- chapter 7 Performance of Self-Propelled Intercultivator / Uddhao S. Kankal M. Anantachar V. K. Chavan -- part, Management of Natural Resources / Megh R. Goyal -- chapter 8 Agro-Biodiversity Collection and Conservation From Arid and Semi-Arid Regions of India / Raju R. Meghwal N. K. Dwivedi -- chapter 9 Watershed Development and Management / R. K. Sivanappan -- chapter 10 Water Resources of India: Problems, Solutions, and Prospects / R. K. Sivanappan -- chapter 11 Present Status of Water Resources in Tamil Nadu / R.K. Sivanappan -- chapter 12 Water Conservation and Increased Crop Production Under Precision Farming / R. K. Sivanappan -- part, Principles of Soil and Water Engineering / Megh R. Goyal -- chapter 13 Basics of Soil and Water Conservation Engineering / R. K. Sivanappan.
Keywords: Agricultural engineering